The application of complexity theory to contracting out public health interventions : a thesis presented in fulfilment of the requirements for the degree of Master of Philosophy, School of Health at Massey University, Wellington, New Zealand - Oakden, Judith Penelope (Massey University, 2019)
The New Zealand government has used a policy approach called New Public Management since the 1980s to contract out public health services. Under this approach contracting out works well for public health services that are predictable, stable and controllable. However, the approach does not always work so well for hard to specify, complex to deliver services, where it is challenging to measure whether the right people benefit. Complexity theorists suggest that public services are complex adaptive systems and therefore do not respond in linear, predictable ways. Complexity theorists also suggest New Public Management framing of contracting out is too simplistic and overlooks the needs of some important population groups, in its quest for efficiency. The overall objective of the research was to explore contracting out of public health services using a general complexity framing to see what insights it might add. The research considered: which ideas from within complexity theory might provide a possible frame to examine contracting out practices; how complexity theory might inform contracting out practice for public health services; and how public sector managers might understand the processes and dynamics of contracting out if informed by complexity theory. A review of complexity and public management literature identified four complexity concepts used to frame interview questions and analyse results for this research: path dependence, emergence, self-organisation and feedback. A small-scale qualitative study used a theory-based approach to test the complexity concepts with public sector managers experienced in contracting out for public health and social services. This research argues that a framing informed by complexity theory resonated with public sector managers in understanding and working in the messy ‘realities’ of contracting out. This research observes that contracting out is often not tidy, linear and controllable as suggested by New Public Management practices. Public sector managers seeking to try new contracting out approaches, can find the underlying New Public Management ethos found in many administrative arms of government hampers them. This research provides insights about why change is hard to achieve, as well as offering public sector managers some alternative ways to think about how they contract out public health services.
Keywords: Public health; Government policy; New Zealand; Medical care; Contracting out; Public health administration; Health services administration; Complexity (Philosophy)